2016
DOI: 10.5114/aoms.2016.59929
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular diseases in patients 65 years and younger with non-cardiogenic stroke

Abstract: IntroductionApproximately 10–15% of patients with stroke are under 65 years of age. The aim of the study was to determine types of stroke In people below 65. We analysed the incidence and types of associated cardiovascular diseases in patients with non-cardiogenic stroke.Material and methodsIn this prospective study patients (aged ≤ 65) with stroke underwent physical examination, computed tomography of the head, blood tests, electrocardiogram, echocardiography, and transcranial and carotid artery ultrasound. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Atrial fibrillation (AF) is the most common arrhythmia in the clinical setting and can induce several cardiovascular complications, including stroke, heart failure, and myocardial infarction [14], which results in increased mortality and public health costs [5]. Structural remodelling has been observed in both clinical and experimental AF paradigms and is an important feature of the AF substrate, producing fibrosis that alters atrial tissue composition and function.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common arrhythmia in the clinical setting and can induce several cardiovascular complications, including stroke, heart failure, and myocardial infarction [14], which results in increased mortality and public health costs [5]. Structural remodelling has been observed in both clinical and experimental AF paradigms and is an important feature of the AF substrate, producing fibrosis that alters atrial tissue composition and function.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of studies have previously assessed the relationship between FHx and IMT [50], none has investigated this relationship in the absence of all TRF, and none has measured atherosclerosis burden. Because most cardiovascular events are not predicted by risk factor profiles [51], it is very important to have better methods to identify high-risk patients who would be likely to benefit most from preventive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Competing causes of IS/TIA in AF patients, such as carotid atherosclerosis and/or cerebral small vessel disease, have been reported in approximately 25% of cases [ 28 ]. We also demonstrated that competing causes are even more common in AFl, because 56% of the patients with AFl in our cohort had more than one evident mechanism of IS.…”
Section: Discussionmentioning
confidence: 99%